Effect of long-lasting insecticidal nets with and without piperonyl butoxide on malaria indicators in Uganda (LLINEUP): a pragmatic, cluster-randomised trial embedded in a national LLIN distribution campaign. Issue 10232 (18th April 2020) - Staedke, Sarah G; Gonahasa, Samuel; Dorsey, Grant; Kamya, Moses R; Maiteki-Sebuguzi, Catherine; Lynd, Amy; Katureebe, Agaba; Kyohere, Mary; Mutungi, Peter; Kigozi, Simon P; Opigo, Jimmy; Hemingway, Janet; et al.
Summary: Background: Long-lasting insecticidal nets (LLINs) are the primary malaria prevention tool, but their effectiveness is threatened by pyrethroid resistance. We embedded a pragmatic cluster-randomised trial into Uganda's national LLIN campaign to compare conventional LLINs with those containing piperonyl butoxide (PBO), a synergist that can partially restore pyrethroid susceptibility in mosquito vectors. Methods: 104 health sub-districts, from 48 districts in Uganda, were randomly assigned to LLINs with PBO (PermaNet 3.0 and Olyset Plus) and conventional LLINs (PermaNet 2.0 and Olyset Net) by proportionate randomisation using an iterative process. At baseline 6, 12, and 18 months after LLIN distribution, cross-sectional surveys were done in 50 randomly selected households per cluster (5200 per survey); a subset of ten households per cluster (1040 per survey) were randomly selected for entomological surveys. The primary outcome was parasite prevalence by microscopy in children aged 2–10 years, assessed in the as-treated population at 6, 12, and 18 months. This trial is registered with ISRCTN, ISRCTN17516395. Findings: LLINs were delivered to households from March 25, 2017, to March 18, 2018, 32 clusters were randomly assigned to PermaNet 3.0, 20 to Olyset Plus, 37 to PermaNet 2.0, and 15 to Olyset Net. In the as-treated analysis, three clusters were excluded because no dominant LLIN was received, and four clusters were reassigned, resulting in 49 PBO LLIN clusters (31 received PermaNet 3.0 and 18 received Olyset Plus) and 52 non-PBO LLIN clusters (39 received PermaNet 2.0 and 13 received Olyset Net). At 6 months, parasite prevalence was 11% (386/3614) in the PBO group compared with 15% (556/3844) in the non-PBO group (prevalence ratio [PR] adjusted for baseline values 0·74, 95% CI 0·62–0·87; p=0·0003). Parasite prevalence was similar at month 12 (11% vs 13%; PR 0·73, 95% CI 0·63–0·85; p=0·0001) and month 18 (12% vs 14%; PR 0·84, 95% CI 0·72–0·98; p=0·029). Interpretation: In Uganda, where pyrethroid resistance is high, PBO LLINs reduced parasite prevalence more effectively than did conventional LLINs for up to 18 months. This study provides evidence needed to support WHO's final recommendation on use of PBO LLINs. Funding: The Against Malaria Foundation, UK Department for International Development, Innovative Vector Control Consortium, and Bill and Melinda Gates Foundation.